Sourcebook of contemporary fashion design - Hidalgo, Marta (New York, NY : HarperCollins Publishers, 2010)
An anthology featuring more than 300 fashion designers around the world. It contains the case studies incorporating different types of design projects - from the t-shirt to the evening dress, from shoes to handbags, hats to jewellery. It is suitable for consumers, designers, design students, fashion retailers, merchandisers, and stylists.
boek